Debranching of waxy maize starches by pullulanase, and structure and digestibility of spherulites formed - Shi, Jialiang (Kansas State University, 2016)
Resistant starch (RS) is notable for having several health benefits in humans, including glucose control and intestinal well-being. Pullulanase is able to debranch amylopectin and result in higher RS content. Different levels of pullulanase have been used to debranch waxy maize starch in the literature, but the changes of structure during debranching are well documented. In this study, waxy maize starch was cooked and debranched by pullulanase with 80, 160 and 240 New Pullulanase Unit Novo (NPUN)/g starch pullulanase. One NPUN was defined as the amount of enzyme, which, under standard conditions, hydrolyzes pullulan, liberating reducing carbohydrate with reducing power equivalent to 1 µmole glucose per minute. The structure of waxy maize starch during debranching was investigated and the digestibility of the debranched products was measured. When pullulanase was increased from 80 to 240 NPUN/g, more amylopectin was debranched in the same debranching time, and the degree of crystallinity and the RS content increased. After the debranched starches were crystallized at 25°C for 24 hours, the RS contents were greater than 63%. When heated and recrystallized under highly regulated conditions, the linear material formed crystallites of a range of geometries, including spherulites of a highly organized structure. Debranched waxy maize starches were used to produce crystalline structure under four conditions: spherulites formed by adding ethanol and crystallized at 4°C (ES4); spherulites formed in water (WS4) at 4°C; particles formed at 50°C (WS50); and spherulites formed at 50°C then further precipitated at 4°C (WS50-4). Spherulites formed at 50°C (WS50) had a higher proportion of smaller molecules than existed in the parent starch (Rh<15nm). ES4 and WS4 were B-type crystalline structure; whereasWS50 and WS50-4 were A-type crystalline structure. ES4 had a larger proportion of molecules with a low degree of polymerization and the RS content was also the lowest of the four samples. With cooling from 50°C to 4°C (WS50-4), the RS content was increased from 60% to 73%. ES4 and WS50-4 contained particles with spherical symmetry and WS4 had partial radial symmetry with some distortions, whereas WS50 displayed oblate particles with a parallel crystal structure.
Keywords: Starch; Resistant starch; Digestibility; Spherulite